2022
DOI: 10.3389/fneur.2022.874193
|View full text |Cite
|
Sign up to set email alerts
|

Dural Immune Cells, CGRP, and Migraine

Abstract: Migraine is the most common neurological disorder in the world, affecting 12% of the population. Migraine involves the central nervous system, trigeminal nerves and meninges. Recent advances have shown that targeting calcitonin gene-related peptide (CGRP) through either antibodies or small molecule receptor antagonists is effective at reducing episodic and chronic migraine episodes, but these therapeutics are not effective in all patients. This suggests that migraine does not have a singular molecular cause bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 139 publications
1
15
0
Order By: Relevance
“…TRESK activation / overexpression does not only modulate the firing rate but also inhibits the release of substance P and the vasodilative peptide CGRP [61,[63][64][65]. Both peptides act as important neurotransmitters and are involved in pain transmission and in (neuro)inflammation [66,67]. Thus, TRESK function might play an important role in distinct inflammatory processes as well, which is strengthened by many different studies [33,[68][69][70][71].…”
Section: Expression Pattern and Physiological Relevance Of Treskmentioning
confidence: 93%
“…TRESK activation / overexpression does not only modulate the firing rate but also inhibits the release of substance P and the vasodilative peptide CGRP [61,[63][64][65]. Both peptides act as important neurotransmitters and are involved in pain transmission and in (neuro)inflammation [66,67]. Thus, TRESK function might play an important role in distinct inflammatory processes as well, which is strengthened by many different studies [33,[68][69][70][71].…”
Section: Expression Pattern and Physiological Relevance Of Treskmentioning
confidence: 93%
“…Furthermore, the action of CGRP on pericytes at the endothelial levels determines an increase in the permeability of meningeal arteries [ 27 ]. Furthermore, the degranulation of meningeal mast cells has been linked to trigeminal nerve fiber activation [ 28 ]. It should be noticed that meningeal immune cells and CGRP are a growing field of research, but their relationship has not been completely unveiled yet.…”
Section: Current Understanding Of Migraine Pathophysiology With Relev...mentioning
confidence: 99%
“…It should be noticed that meningeal immune cells and CGRP are a growing field of research, but their relationship has not been completely unveiled yet. Despite this, readers may find an exhaustive review on this topic [ 28 ]. Moreover, CGRP also binds upon its receptors located on the Aδ-fibers, thus activating the PKA pathway and, consequently, trigeminal fiber sensitization [ 29 ].…”
Section: Current Understanding Of Migraine Pathophysiology With Relev...mentioning
confidence: 99%
“…Meningeal tissues contain various immune cells [ 77 , 78 ]. Of special interest are local mast cells which synthesize a plethora of active molecules including ATP, hormones, cytokines, neurotrophins, all to be released in a stimulus-specific manner [ 79 , 80 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the neuropeptide CGRP is considered a major contributor to the onset of migraine attacks [ 12 ] and has multifarious effects on neurons and immune cells in the CNS [ 78 ], we propose that one important target for the CGRP algogenic action is the P2X3 receptor. Progress in understanding the molecular mechanisms of such an action of CGRP has come from the use of an in vitro model of mouse trigeminal ganglia where it has been shown that CGRP (at submicromolar concentrations) selectively binds to sensory neurons expressing P2X3 receptors without generating any direct change in their membrane current [ 16 , 93 ].…”
Section: Introductionmentioning
confidence: 99%